Alternative forms of portal vein revascularization in liver transplant recipients with complex portal vein thrombosis - Fundora, Yiliam; Hessheimer, Amelia J; Del Prete, Luca; Maroni, Lorenzo; Lanari, Jacopo; Barrios, Oriana; Clarysse, Mathias; Gastaca, Mikel; Barrera Gómez, Manuel; Bonadona, Agnès; Janek, Julius; Boscà, Andrea; et al. (Journal of hepatology, 2023)
BACKGROUND & AIMS: Complex portal vein thrombosis (PVT) is a challenge in liver transplantation (LT). Extra-anatomical approaches to portal revascularization, including renoportal (RPA), left gastric vein (LGA), pericholedochal vein (PCA), and cavoportal (CPA) anastomoses, have been described in case reports and series. The RP4LT Collaborative was created to record cases of alternative portal revascularization performed for complex PVT. METHODS: An international, observational web registry was launched in 2020. Cases of complex PVT undergoing first LT performed with RPA, LGA, PCA, or CPA were recorded and updated through 12/2021. RESULTS: A total of 140 cases were available for analysis: 74 RPA, 18 LGA, 20 PCA, and 28 CPA. Transplants were primarily performed with whole livers (98%) in recipients with median (IQR) age 58 (49-63) years, model for end-stage liver disease score 17 (14-24), and cold ischemia 431 (360-505) minutes. Post-operatively, 49% of recipients developed acute kidney injury, 16% diuretic-responsive ascites, 9% refractory ascites (29% with CPA, p <0.001), and 10% variceal hemorrhage (25% with CPA, p = 0.002). After a median follow-up of 22 (4-67) months, patient and graft 1-/3-/5-year survival rates were 71/67/61% and 69/63/57%, respectively. On multivariate Cox proportional hazards analysis, the only factor significantly and independently associated with all-cause graft loss was non-physiological portal vein reconstruction in which all graft portal inflow arose from recipient systemic circulation (hazard ratio 6.639, 95% CI 2.159-20.422, p = 0.001). CONCLUSIONS: Alternative forms of portal vein anastomosis achieving physiological portal inflow (i.e., at least some recipient splanchnic blood flow reaching transplant graft) offer acceptable post-transplant results in LT candidates with complex PVT. On the contrary, non-physiological portal vein anastomoses fail to resolve portal hypertension and should not be performed. IMPACT AND IMPLICATIONS: Complex portal vein thrombosis (PVT) is a challenge in liver transplantation. Results of this international, multicenter analysis may be used to guide clinical decisions in transplant candidates with complex PVT. Extra-anatomical portal vein anastomoses that allow for at least some recipient splanchnic blood flow to the transplant allograft offer acceptable results. On the other hand, anastomoses that deliver only systemic blood flow to the allograft fail to resolve portal hypertension and should not be performed.
Keywords: transplantace jater; Hypertension, Portal; ascites; stupeň závažnosti nemoci; Esophageal and Gastric Varices; vena portae; Middle Aged; End Stage Liver Disease; ezofageální a žaludeční varixy; Ascites; portální hypertenze; Portal Vein; Gastrointestinal Hemorrhage; žilní trombóza; gastrointestinální krvácení; Humans; Liver Transplantation; lidé středního věku; konečné stadium selhání jater; Venous Thrombosis; Severity of Illness Index; lidé